Desmoid tumor of the rectus abdominis mimicking a rectus sheath hematoma - Bakoban, Khaled Abdul Rahman; Anjum, Mahiya; Patil, Sharan (International Surgery Journal, 2026)
Aggressive fibromatosis, a synonym for desmoid tumours, is a rare kind of fibroblastic growth. Any musculoaponeurotic structure in the body may develop these tumours. They are categorized as benign because of a number of unique characteristics, including regular mitotic activity and no potential for metastasis but local recurrence is not uncommon. Surgical excision is highly recommended, and computed tomography (CT) is a valuable imaging modality. This report describes the appearance of a desmoid tumor in the anterior abdominal wall of a female patient, age 28, who had three prior caesarean sections. The procedure involved removing the tumor and then using polypropylene mesh to rebuild the abdominal wall. The patient was discharged 3 days post-surgery with no adverse complications and a follow up was done 6 months.